2008
DOI: 10.1093/erae/jbn017
|View full text |Cite
|
Sign up to set email alerts
|

Economic development in emerging Asian markets: implications for Europe

Abstract: The impacts of faster growth in China and India for Europe are analysed taking into account terms-of-trade effects, second-best welfare impacts and improvements in product quality and variety. More rapid growth in these giants could improve Europe's terms of trade, but second-best effects on energy markets could lower welfare unless these taxes are Pigovian. Whether growth arises from productivity or capital accumulation has important implications, with capital-driven growth involving higher energy and agricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…In the same direction, Devadason (2010), analyzing intra-ASEAN trade, concluded that there is no evidence of diversion away from intra-ASEAN trade to ASEAN-China trade, since the coefficient that represents China's competition was negative, but statically insignificant. Besides, the studies that investigated the implications of industrial exporting power recently achieved by China on Asian countries, there is research that covers other global locations, such as Africa (Broadman, 2007;Giovanetti & Sanfilippo, 2009;Edwards & Jenkins, 2014), Europe (Martin, Ianchovichina, & Dimaranan, 2008), Russia (Ianchovichina, Ivanic, & Martin, 2009), Mexico (Gallagher, Moreno-Brid, & Porzecanski, 2008), among other countries and continents. In that sense, Ianchovichina and Martin (2006) point out that Chinese competition is important not only to South and South-East Asian countries, but also to Latin America, with the possibility of relevant losses to these countries.…”
Section: Módolo and Hiratukamentioning
confidence: 99%
“…In the same direction, Devadason (2010), analyzing intra-ASEAN trade, concluded that there is no evidence of diversion away from intra-ASEAN trade to ASEAN-China trade, since the coefficient that represents China's competition was negative, but statically insignificant. Besides, the studies that investigated the implications of industrial exporting power recently achieved by China on Asian countries, there is research that covers other global locations, such as Africa (Broadman, 2007;Giovanetti & Sanfilippo, 2009;Edwards & Jenkins, 2014), Europe (Martin, Ianchovichina, & Dimaranan, 2008), Russia (Ianchovichina, Ivanic, & Martin, 2009), Mexico (Gallagher, Moreno-Brid, & Porzecanski, 2008), among other countries and continents. In that sense, Ianchovichina and Martin (2006) point out that Chinese competition is important not only to South and South-East Asian countries, but also to Latin America, with the possibility of relevant losses to these countries.…”
Section: Módolo and Hiratukamentioning
confidence: 99%
“…The main reasons for the increasing real prices of food and agricultural products are increasing population, income growth, and shifts in food diets towards livestock products in countries with rapidly increasing incomes and low initial share of livestock products. This reasoning is also shared by Martin et al (2008), showing increasing specialization in agricultural production between different countries and production regions as well.…”
Section: Socio-economic Drivers Of Crop Yieldsmentioning
confidence: 76%
“…global warming, leading to a gradually increasing length and temperature sum (accumulated degree days when average daily temperature during the growing period exceeds 5 degrees Celsius) of the growing period in northern Europe (Ruosteenoja et al 2010), and another is the gradually increasing global demand for food, driven by an increasing global population and higher income levels, implying a possible increase in the real prices of food (FAO 2012, Godfray et al 2011, Tilman et al 2011. Increasing incomes worldwide implies a more inelastic food demand which contributes to higher price volatility on food markets (Martin et al 2008). Climate change is expected to increase potential yields in northern Europe (Peltonen-Sainio et al 2009, Olesen et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…This work (see Martin 2007, 2009) highlighted the benefits to other developing countries from increases in their direct trade and the potentially adverse impacts of greater competition in third markets. Our work on Europe highlighted the benefits from direct trade, and some interesting interactions of changes on energy prices and domestic taxation policies for energy (Martin, Ianchovichina and Dimaranan 2008). In this paper, and in related work on the Middle East (Ianchovichina, Ivanic and Martin 2008), we pay more attention to impacts through changes in the prices of resources resulting from the growth of China and India.…”
Section: Introductionmentioning
confidence: 97%